2007
DOI: 10.1111/j.1365-2621.2006.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean variety and storage effects on soymilk flavour and quality

Abstract: Soymilk prepared from five soybean cultivars, grown in Ontario, were analysed for protein, oil, mineral composition, viscosity, colour, lipoxygenase (LOX) activities and flavour profile. Among the five soybean cultivars, the Vinton 81 variety contained the highest protein and the lowest fat. The yield of soymilk from all five cultivars was similar. Major differences were observed in viscosity and in the composition of both the soymilk and the okara. Higher protein and fat extractability was found in soymilk ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
(38 reference statements)
3
14
0
2
Order By: Relevance
“…Viscosity ranged from 2.7 (DSb1-sprouted) to 3.2 (JS335 Ranchi raw). The results are similar to earlier studies (Achouri et al 2008) and the decrease could be due to increased solubility of proteins, decrease in fat content on sprouting (Agrahar Murugkar and Jha 2009).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Viscosity ranged from 2.7 (DSb1-sprouted) to 3.2 (JS335 Ranchi raw). The results are similar to earlier studies (Achouri et al 2008) and the decrease could be due to increased solubility of proteins, decrease in fat content on sprouting (Agrahar Murugkar and Jha 2009).…”
Section: Resultssupporting
confidence: 91%
“…These observations could be explained considering the fact that during sprouting, there is a breakdown of reserve protein to give NH 3 , which accumulates, in the form of amide such as glutamic acid and aspartic acid (Hsu et al 1980) while depletion of the fat stored is due to the catabolic activities of the seeds during sprouting Mostafa et al (1987) which agrees with our results. Fat content value in soymilk prepared be raw seeds were similar a reported by Achouri et al (2008). Sprouting can degrade both Kunitz soybean trypsin inhibitor and the major Bowman-Birk soybean trypsin inhibitor (Collins and Sand 1976) due to the proteolytic activity of enzymes, which are activated during sprouting (Chauhan and Chauhan 2007).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Por ser uma bebida sem lactose e com ácidos graxos poli-insaturados é ideal para portadores de intolerância à lactose ou indivíduos com índice de colesterol alto (GUERREIRO, 2006;MAIA et al, 2006). Segundo Achouri et al (2008) e Axerold et al (1981), a população ocidental não tem o hábito de consumir produtos à base de soja, os quais são descritos como amargos e adstringentes (beany flavor). A soja e seus derivados apresentam sabor e odor característico em consequência da ação das lipoxigenases, enzimas capazes de oxidar os ácidos graxos poli-insaturados, os quais são metabolizados em substâncias voláteis.…”
Section: Introductionunclassified
“…SAIO et al (1980) For grains stored at 30 ºC and relative humidity of 84.0%, the authors observed a reduction in yield (512g/100g of grains at time zero to 71g/100 g of grains after 7 months of storage) and alterations in texture with increasing hardness and color (Table 10). ACHOURI et al (2008) evaluated the quality of the soymilk obtained from soybeans stored for 10 months at 18 ºC and 50% relative humidity. Under these storage conditions the authors observed no significant change in the water uptake factor and pH of the soymilk, but there was significant variation in color and total volatiles.…”
Section: Effects Of Different Storage Conditions On the Quality Of Otmentioning
confidence: 99%